LANGUAGE PIDGINIZATION FEATURES IN THE CONTEXT OF LANGUAGE INTERACTION (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-105-117The article examines the specifics of such linguistic phenomena as pidginization and creolization. The aim of the research work is to identify the key properties of the Pidgin English functioning in Ghana, one of the largest countries in West Africa. In the context of cross cultural interaction with local linguistic cultures in African countries, English has remained a foreign language for a long period inaccessible to the vast majority of the population, which has led to the need for its linguistic and cultural adaptation and significant simplification in use as a means of daily communication. The result of the interaction of numerous languages and cultures of Ghana and British English the pidgin English of Ghana was created. This langauge variant is characterized by simplification at all levels. As a result of the research work functional features of the Pidgin English of Ghana were revealed which are as following: reduction and epentesis at the phonetic level; reduplication at the morphological level; direct word order at the syntactic level; expansion of the word meaning for lexical level. The results of the research work can be used as theoretical and practical material to study the phenomena of pidginization and creolization on the example of other African countries, such as Nigeria, Gambia, Sierra Leone, Malawi, Zambia, Zimbabwe, Botswana, Le Soto, etc. Key words: Pidginization, Creolization, British English, Pidgin English, pidgin English of Ghana